Q. 20 D4.8( 5 Votes )

# Let r and n be positive integers such that 1 ≤ r ≤ n. Then prove the following:nCr + 2nCr – 1 + nCr – 2 = n + 2Cr

Given that we need to prove nCr + 2nCr – 1 + nCr – 2 = n + 2Cr

Consider L.H.S,

We know that nCr + nCr + 1 = n + 1Cr + 1

nCr + 2nCr – 1 + nCr – 2 = (nCr + nCr – 1) + (nCr – 1 + nCr – 2)

nCr + 2nCr – 1 + nCr – 2 = n + 1Cr + n + 1Cr – 1

nCr + 2nCr – 1 + nCr – 2 = n + 2Cr

= R.H.S

L.H.S = R.H.S, thus proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Permutations & Combinations | Analyze your learningFREE Class
Challenging Quiz on P&C | Test Yourself55 mins
Understand Permutations like never before60 mins
Check Your progress Part 2| Interactive Quiz: Permutation & Combination54 mins
Lecture on Combinations49 mins
Interactive Quiz on Division and distribution of objects17 mins
Interactive Quiz on Combinations50 mins
Lets see how good you can manage numbers | P&C Quiz Challenge41 mins
Ladoo Bhikhari Concept46 mins
Indepth Understanding of Factorials56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses